Dietary fat content and absorption shape standard diet devaluation through hunger circuits - Ames K. Sutton Hickey; Jordan Becker; Eva O. Karolczak; Andrew Lutas; Michael J. Krashes (Elsevier, 2024)
Objective: Exposure to 60% high fat diet (HFD) leads to a robust consummatory preference over well-balanced chow standard diet (SD) when mice are presented with a choice. This passive HFD-induced SD devaluation following HFD challenge and withdrawal is highlighted by the significant reduction in SD food intake even in states of caloric deprivation. The elements of HFD that lead to this SD depreciation remains unclear. Possibly important factors include the amount and type of fat contained in a diet as well as past eating experiences dependent on sensory properties including taste and post ingestive feedback. We aimed to explore the role of these components to HFD-induced SD devaluation. Methods: Wildtype mice were longitudinally presented discrete HFDs in conjunction with SD and feeding and metabolic parameters were analyzed. A separate cohort of animals were assessed for acute HFD preference in 3 conditions: 1) ad libitum fed (sated), 2) overnight fasted (physiologically hungry), and 3) ad libitum fed (artificially hungry), elicited through chemogenetic Agouti-related peptide (AgRP) neuron activation. Population dynamics of AgRP neurons were recorded to distinct inaccessible and accessible diets both before and after consummatory experience. Transient receptor potential channel type M5 (TRPM5) knockout mice were used to investigate the role of fat taste perception and preference to HFD-induced SD devaluation. The clinically approved lipase inhibitor orlistat was used to test the contribution of fat absorption to HFD-induced SD devaluation. Results: HFD-induced SD devaluation is dependent on fat content, composition, and preference. This effect scaled both in strength and latency with higher percentages of animal fat. 60% HFD was preferred and almost exclusively consumed in preference to other diets across hours and days, but this was not as evident upon initial introduction over seconds and minutes, suggesting ingestive experience is critical. Optical fiber photometry recordings of AgRP activity supported this notion as neuronal suppression by the different diets was contingent on prior intake. While taste transduced via TRPM5 influenced HFD-evoked weight gain, it failed to impact either HFD preference or HFD-induced SD devaluation. Perturbation of post ingestive feedback through orlistat-mediated diminishment of fat absorption prevented HFD-evoked weight gain and abolished HFD-induced SD devaluation. Conclusions: Post ingestive feedback via fat digestion is vital for expression of HFD-induced SD devaluation.